Single priming and booster dose of ten-valent and 13-valent pneumococcal conjugate vaccines and Streptococcus pneumoniae colonisation in children in South Africa: a single-centre, open-label, randomised trial. (May 2023) - Olwagen, Courtney P; Izu, Alane; Mutsaerts, Eleonora A M L; Jose, Lisa; Koen, Anthonet; Downs, Sarah L; Van Der Merwe, Lara; Laubscher, Matt; Nana, Amit J; Moultrie, Andrew; Cutland, Clare L; Dorfman, Jeffrey R; et al.
Summary: Background: Pneumococcal conjugate vaccine (PCV) immunisation has reduced vaccine-serotype colonisation and invasive pneumococcal disease in South Africa, providing the opportunity to consider transitioning from a two-dose (2 + 1) to one-dose (1 + 1) primary series and a booster dose. Methods: In this single-centre, open-label, randomised trial done in South Africa, infants aged 35–49 days without HIV infection, without childhood immunisations except for BCG and polio, and with gestation age at delivery of at least 37 weeks of age, a birthweight of at least 2500 g, and weight of at least 3500 g at the time of enrolment were randomly assigned (1:1:1:1:1:1), through block randomisation (block size of 30), to receive a single priming dose of ten-valent PCV (PCV10) or 13-valent PCV (PCV13) at either 6 weeks (6-week 1 + 1 group) or 14 weeks (14-week 1 + 1 group), compared with two priming doses at 6 weeks and 14 weeks (2 + 1 group), followed by a booster dose at 9 months of age in all groups. The primary objective of the trial has been published previously. We report the secondary objective of the effect of alternative doses of PCV10 and PCV13 on serotype-specific Streptococcus pneumoniae colonisation at 9 months, 15 months, and 18 months of age and a further exploratory analysis in which we assessed non-inferiority of serotype-specific serum IgG geometric mean concentrations 1 month after the booster (10 months of age) and the percentage of participants with serotype-specific IgG titre above the putative thresholds associated with a risk reduction of serotype-specific colonisation between the 1 + 1 and 2 + 1 groups for both vaccines. Non-inferiority was established if the lower limit of the 95% CI for the difference between the proportion of participants (1 + 1 group vs 2 + 1 group) above the putative thresholds was greater than or equal to –10%. All analyses were done in the modified intention-to-treat population, which included all participants who received PCV10 or PCV13 according to assigned randomisation group and for whom laboratory results were available. The trial is registered with ClinicalTrials.gov, NCT02943902 . Findings: 1564 nasopharyngeal swabs were available for molecular serotyping from 600 infants who were enrolled (100 were randomly assigned to each of the six study groups) between Jan 9 and Sept 20, 2017. There was no significant difference in the prevalence of overall or non-vaccine serotype colonisation between all PCV13 or PCV10 groups. PCV13 serotype colonisation was lower at 15 months of age in the 14-week 1 + 1 group than in the 2 + 1 group (seven [8%] of 85 vs 17 [20%] of 87; odds ratio 0·61 [95% CI 0·38–0·97], p=0·037), but no difference was seen at 9 months (nine [11%] of 86 vs ten [11%] of 89; 0·92 [0·60–1·55], p=0·87) or 18 months (nine [11%] of 85 vs 11 [14%] of 87; 0·78 [0·45–1·22], p=0·61). Compared with the PCV13 2 + 1 group, both PCV13 1 + 1 groups did not meet the non-inferiority criteria for serotype-specific anti-capsular antibody concentrations above the putative thresholds purportedly associated with risk reduction for colonisation; however, the PCV10 14-week 1 + 1 group was non-inferior to the PCV10 2 + 1 group. Interpretation: The serotype-specific colonisation data reported in this study together with the primary immunogenicity endpoints of the control trial support transitioning to a reduced 1 + 1 schedule in South Africa. Ongoing monitoring of colonisation should, however, be undertaken immediately before and after transitioning to a PCV 1 + 1 schedule to serve as an early indicator of whether PCV 1 + 1 could lead to an increase in vaccine-serotype disease. Funding: The Bill & Melinda Gates Foundation.